2000
DOI: 10.1021/np990412p
|View full text |Cite
|
Sign up to set email alerts
|

Studies Directed toward the Synthesis of Cryptoheptine

Abstract: Synthesis of 5,10-dihydro-10-methylindolo[3, 2-b][1]benzazepin-12(11H)-one (2), an isomer of the reported structure for cryptoheptine (1), is presented. Attempts to convert 2 to 1 led to 10-methylindolo[3,2-b][1]benzazepin-12-one (10), an oxidation product of 2 and presumably 1. These results highlight the potential instability of cryptoheptine and cast doubt on its proposed structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…As we were unable to oxidatively cleave the indole in dehydroDKP 8 , an alternative synthesis of the model furopyrazine precursor 9 was developed (Scheme ). Selenium dioxide-mediated oxidation of o -nitroacetophenone gave the glyoxal 12 , which underwent condensation with the DKP 13 to give enedione 14 as a single Z -isomer . Acid-mediated cleavage of the remaining acetamide, followed by reduction gave aniline 15 , the precursor for the key biomimetic furopyrazine formation.…”
Section: Resultsmentioning
confidence: 99%
“…As we were unable to oxidatively cleave the indole in dehydroDKP 8 , an alternative synthesis of the model furopyrazine precursor 9 was developed (Scheme ). Selenium dioxide-mediated oxidation of o -nitroacetophenone gave the glyoxal 12 , which underwent condensation with the DKP 13 to give enedione 14 as a single Z -isomer . Acid-mediated cleavage of the remaining acetamide, followed by reduction gave aniline 15 , the precursor for the key biomimetic furopyrazine formation.…”
Section: Resultsmentioning
confidence: 99%
“…It was noteworthy that direct reaction of 4aa with 1.2 equiv of I 2 and 2.4 equiv of DMAP led to a complex mixture with very low conversion. To the best our knowledge, the benzoazepinone skeleton like 11 and 12 was rather rare . If 4aa was heated in a mixed solvent of DMSO/H 2 O (4:1) in the presence of catalytic amounts of hydrochloric acid at 90 °C for 22 h, two interesting cyclization products 13 and 14 were provided in 46% and 30% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To the best our knowledge, the benzoazepinone skeleton like 11 and 12 was rather rare. 16 If 4aa was heated in a mixed solvent of DMSO/H 2 O (4:1) in the presence of catalytic amounts of hydrochloric acid at 90 °C for 22 h, two interesting cyclization products 13 17 and 14 were provided in 46% and 30% yield, respectively. During the reaction, 11 was quickly formed as the intermediate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been demonstrated that the proposed structure 86a for cryptoheptine is doubtful. 55 Scheme 21 Reagents: i, cat. piperidine, toluene, rt; ii, 10% HCl, THF, reflux; iii, NaH, DMF, Ϫ10 ЊC, then MeI; iv, H 2 , Pd/C, toluene; v, p-TsOH, toluene, Dean-Stark.…”
Section: Indoloquinolines and Related Compoundsmentioning
confidence: 99%